2012
DOI: 10.1128/jvi.06187-11
|View full text |Cite
|
Sign up to set email alerts
|

Role of Multiple Hosts in the Cross-Species Transmission and Emergence of a Pandemic Parvovirus

Abstract: Understanding the mechanisms of cross-species virus transmission is critical to anticipating emerging infectious diseases. Canine parvovirus type 2 (CPV-2) emerged as a variant of a feline parvovirus when it acquired mutations that allowed binding to the canine transferrin receptor type 1 (TfR). However, CPV-2 was soon replaced by a variant virus (CPV-2a) that differed in antigenicity and receptor binding. Here we show that the emergence of CPV involved an additional host range variant virus that has circulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(134 citation statements)
references
References 33 publications
(38 reference statements)
9
121
2
2
Order By: Relevance
“…The regaining of the feline host range and infection of other hosts is likely to be a selective advantage for the virus (Truyen et al, 1996a). While CPV-2 is considered a host range variant of a virus closely related to FPV that gained the ability to infect dogs via wild carnivores, as previously reported, the emergence of CPV-2a was previously suggested to be due to host adaptation in dogs (Allison et al, 2012). A recent study (Allison et al, 2012) showed that raccoons from the USA have harboured parvoviruses similar to CPV for over 20 years.…”
Section: Other Vp2 Mutations Reported In the Antigenic Variantsmentioning
confidence: 78%
See 3 more Smart Citations
“…The regaining of the feline host range and infection of other hosts is likely to be a selective advantage for the virus (Truyen et al, 1996a). While CPV-2 is considered a host range variant of a virus closely related to FPV that gained the ability to infect dogs via wild carnivores, as previously reported, the emergence of CPV-2a was previously suggested to be due to host adaptation in dogs (Allison et al, 2012). A recent study (Allison et al, 2012) showed that raccoons from the USA have harboured parvoviruses similar to CPV for over 20 years.…”
Section: Other Vp2 Mutations Reported In the Antigenic Variantsmentioning
confidence: 78%
“…The phylogenetic relationships between CPV-2 isolates from dogs and the viruses from cats (FPV), mink (MEV), raccoon (RPV), raccoon dog (Raccoon dog parvovirus, RDPV) and blue fox (Blue fox parvovirus, BFPV) showed that all CPVs derived from a single common ancestor, and that the strains were mostly similar to viruses from different wildlife animals including raccoons and foxes (Allison et al, 2012(Allison et al, , 2013. CPV was shown to be related to a virus similar to the long recognized FPV, but likely not from cats (Truyen et al, 1995).…”
Section: Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymorphism in the hypervariable region enables differentiation of strains with varying pathogenicity [12]. The amino acid sequence in this protein may have a significant effect on the range of hosts infected [13], as in the case of CPV-2 [14,15]. The VP2 protein region containing epitopes, due to its significance in pathogenesis as well as its potentially high variability, seems to be a good site in the genome for analysis of polymorphism of the virus in farmed and wild mink populations.…”
Section: Introductionmentioning
confidence: 99%